Chemical composition and biological activities of essential oil of Beilschmiedia pulverulenta. (1st February 2016) - Salleh, Wan Mohd Nuzul Hakimi Wan; Ahmad, Farediah; Yen, Khong Heng; Zulkifli, Razauden Mohamed
Abstract: Context : The ethnopharmacological study of Beilschmiedia indicates that several species are used for the treatment of various ailments. Objective : This is the first study of the chemical composition of Beilschmiedia pulverulenta Kosterm (Lauraceae) essential oil and its antioxidant, antimicrobial, antityrosinase, anti-inflammatory, and anticholinesterase activities. Materials and methods : The antioxidant activities were evaluated by β-carotene, 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging, ferric-reducing antioxidant power (FRAP), and phenolic content at different concentrations. The antimicrobial activities against Gram-positive and Gram-negative bacteria and fungi were revealed by disk diffusion and microdilution. The antityrosinase and anti-inflammatory activities were assayed against mushroom tyrosinase and lipoxygenase enzymes. The anticholinesterase activity was analyzed using acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. Results : Forty-two components were detected in B. pulverulenta oil with eugenol (45.3%) being the major component. The oil phenolic content and the FRAP were 660.1 mg gallic acid/g and 604.0 mg ascorbic acid/g, respectively. The oil gave an IC50 value of 94.5 µg/mL and an inhibition of 93.9% in DPPH and β-carotene, respectively. The antimicrobial activity showed that the oil had strong activity against all Gram-positive bacteria with an minimum inhibitory concentration (MIC) value each of 62.5 µg/mL and moderate against all fungi with MIC and minimum bactericidal concentration (MBC) values each of 125 µg/mL. The oil showed significant antityrosinase and anti-inflammatory activities with 67.6 and 62.5% inhibition, respectively. In addition, the oil had moderate AChE (56.5%) and BChE (48.2%) activities. Discussion and conclusion : The results show that the oil could potentially be used for nutraceutical industries, food manufactures, and therapeutic agents against various diseases such as inflammation and rheumatism.